Mortar Geopolymer Fly Ash dan Karbon Aktif Cangkang Kelapa Sawit - Triana, Dessy (ReTII, 2024)
Environmentally friendly construction development of sustainable and economical building materials. Geopolymers are increasingly in demand, by utilizing waste. Waste materials that mostly contain silicon (Si) and aluminium (Al) are the source materials for making geopolymers. Geopolymers are artificial polymer composites that are environmentally friendly sustainable products. Fly ashas a binder in geopolymers, its physical and chemical characteristics help the geopolymerization reaction. High content of alumino silicate in alkaline. Sustainable building material construction combines industrial and agricultural waste in the form of activated carbon of palm shells. The use of waste materials solves the problem of waste disposal and minimizes the demand for natural resources for mortar production. This study produces geopolymer mortar using fly ash as a substitute for cement and activated carbon of palm shells as a substitute for sand.